Organizations evolving : second edition - Aldrich, Howard E.; Ruef, Martin; Lippmann, Stephen (Los Angeles ; London ; New Delhi : SAGE Publications, 2006)
"Organizations Evolving offers a unique theoretical framework for understanding organizational emergence, persistence, change, and decline. Synthesizing and integrating six paradigmatic approaches to organization theory, this updated and revised third edition presents an evolutionary view that provides a unified understanding of modern organizations and organization theory. Key features of the third edition include: A sophisticated analytic comparison of six major approaches to understanding modern organizations and their evolution An interdisciplinary focus, drawing extensively from sociology, social psychology, economics, history, management and entrepreneurship research Supplementary materials from academic journals and the popular press, and multi-media resources in an online companion Extensive case examples that illustrate key evolutionary processes Study questions designed for extended and reflective learning. Offering key insights and critical learning opportunities, this book is crucial reading for classes covering macro-organizational behaviour and the sociology of organizations. Students of management studies and entrepreneurship, particularly those with a focus on organization theory, will also benefit from its interdisciplinary approach"--